Some considerations on andalusí society and islamic law : in a brief diachronic strokes - Arcas Campoy, María (Estudios de Historia de España, 2017)
This paper aims to show an overall view of the interrelationship between Andalusi society and Islamic Law during the transition from Hispania to al-Andalus until the conquest of Granada in 1492. The questions dealt with here reveal the development of this society that, though plural and heterogenous in many ways, was held together by a single political power under the official cloak of Islam and Arabic, and in whose formation and identity Islamic Law played a vital role, extending far beyond the temporal and geographical space that was al-Andalus